Strategi Pengembangan Kompetensi Guru Dalam Penguasaan Teknologi Pembelajaran - Tengku Darmansah; Hadawiyanti Sinaga; Shakila Putri Suhara; Maulana Harin Hanafi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
The strategy of developing teacher competency in mastering learning technology is very important to improve the quality of education in the digital era. This study highlights various methods that can be applied to strengthen teacher skills, including technology-based training and collaboration between teachers. Through this approach, teachers can develop innovative and interactive lesson plans, utilizing digital tools to increase student engagement. In addition, the application of active learning methods such as projects and educational games can help students hone critical thinking and collaborative skills. This study also emphasizes the importance of stopping in the process of developing teacher competency, so that they can adapt to the changing needs of education. Involvement in professional networks and continuous learning are key to ensuring teachers stay up to date with technological developments. Thus, teacher competency development strategies must include relevant training and support from educational institutions.